2006
DOI: 10.1002/cbf.1250
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in biochemical components of extracellular matrix in intervertebral disc herniation: role of MMP-2 and TIMP-2 in type II collagen loss

Abstract: Alterations in the composition of intervertebral disc extracellular matrix, mainly collagen and proteoglycans, may cause changes in mechanical properties of the disc, leading to dysfunction, nerve root compression, and herniation with severe clinical manifestations. Matrix metalloproteinases may be involved in degradation by hydrolysing extracellular matrix components. Inhibitors of matrix metalloproteinases, in contrast, function in the maintenance of degradation control. In this study, we investigated: (i) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Enhanced expression of MMP-2 has been found in aging and degenerative discs [3,15,23], and MMP-2 production appears to increase when disc cells are exposed to abnormal physical stresses [5].Furthermore, in situ zymography confirmed that gelatinolytic activity was localized in area close to tissue clefts where MMP-2 was expressed at elevated levels [23]. In addition, Kozaci et al reported that Pro-MMP-2 levels were higher at early stages of the degenerative disc disease, which were negatively correlated with the collagen content in herniated disc material [10].…”
Section: Discussionmentioning
confidence: 93%
“…Enhanced expression of MMP-2 has been found in aging and degenerative discs [3,15,23], and MMP-2 production appears to increase when disc cells are exposed to abnormal physical stresses [5].Furthermore, in situ zymography confirmed that gelatinolytic activity was localized in area close to tissue clefts where MMP-2 was expressed at elevated levels [23]. In addition, Kozaci et al reported that Pro-MMP-2 levels were higher at early stages of the degenerative disc disease, which were negatively correlated with the collagen content in herniated disc material [10].…”
Section: Discussionmentioning
confidence: 93%
“…MMP-7 expression by cells of the nucleus and inner anulus has been demonstrated, more so for degenerate discs and those having suffered prolapse than for non-degenerate discs [35]. MMP-2 has been shown to be present in nucleus material from discs suffering from the early stages of degeneration, and also in the vicinity of nuclear clefts and anular tears in degenerate discs [34,70]. MMP-9 has been found to be expressed only at very low levels [70].…”
Section: Roles Of Elastic Fibres In the Ageing And Degeneration Of Thmentioning
confidence: 99%
“…Additionally, MMPs are capable of breaking down certain ECM proteins and thus have an active impact on ECM remodeling via the degradation of matrix scaffold macromolecules (Nissi et al, 2013). MMP-2 belongs to the MMP family, and plays an important role in ECM degradation both directly and indirectly (Kozaci et al, 2006). It is well known that water and collagen are the major components of the IVD, while the ECM of the NP and AF is mainly composed of type 2 collagens (Yurube et al, 2012;Vo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As one important member of the MMP family, MMP-2 actively functions in the secondary breakdown of collagen during the tissue remodeling process (Kozaci et al, 2006;Séguin et al, 2008). Additionally, a large amount of evidence in animal models suggest that MMP-2 is significantly correlated with degenerative changes (Hsieh et al, 2009;Rastogi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation